A review on detection and fault diagnosis in induction machines (Publicaciones en Ciencias y Tecnología, 2014)
In this work a careful review describing diferent types of failures in electricalmachines, their characteristic signals generated and diagnosis methodsis performed. Additionally a comparison of the advantages between theknown failure detection methods based on the information required for diagnosis, the occurrence and importance of failures detection, the effectiveness for anticipating a mal function or failure and the final diagnosis accuracy is also made. Particularly, this review will help to provide a straight forward update about the most recent work and research in this field. The work is mainly oriented to engineering students interested in starting the researchand study of electrical machines.
Keywords: Induction machines; type of failures; characteristics signal generated; failure detection methods; diagnosis methods